Selected peptide-based fluorescent probes for biological applications - Maity, Debabrata (Beilstein Journal of Organic Chemistry, 2020)
To understand the molecular interactions, present in living organisms and their environments, chemists are trying to create novel chemical tools. In this regard, peptide-based fluorescence techniques have attracted immense interest. Synthetic peptide-based fluorescent probes are advantageous over protein-based sensors, since they are synthetically accessible, more stable, and can be easily modified in a site-specific manner for selective biological applications. Peptide receptors labeled with environmentally sensitive/FRET fluorophores have allowed direct detection/monitoring of biomolecules in aqueous media and in live cells. In this review, key peptide-based approaches for different biological applications are presented.
Keywords: fluorescent probe; fluorophores; molecular recognition; peptide-based

(untitled) - Böhm, H.-J.; Klebe, G. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Meyer, E. A.; Castellano, R. K.; Diederich, F. (Angew. Chem., Int. Ed., 2003)

Synthetic Receptors for Biomolecules: Design Principles and Applications - Maity, D.; Schmuck, C. (Synthetic Receptors for Amino Acids and Peptides, 2015)

(untitled) - Wellendorph, P.; Bräuner-Osborne, H. (Br. J. Pharmacol., 2009)

(untitled) - Corti, A.; Curnis, F. (J. Cell Sci., 2011)

(untitled) - Barna, J. C. J.; Williams, D. H. (Annu. Rev. Microbiol., 1984)

(untitled) - Rao, J.; Lahiri, J.; Isaacs, L.; Weis, R. M.; Whitesides, G. M. (Science, 1998)

(untitled) - Christianson, D. W.; Lipscomb, W. N. (J. Am. Chem. Soc., 1986)

(untitled) - Shults, M. D.; Imperiali, B. (J. Am. Chem. Soc., 2003)

(untitled) - Pazos, E.; Vázquez, O.; Mascareñas, J. L.; Eugenio Vázquez, M. (Chem. Soc. Rev., 2009)

(untitled) - Liu, Q.; Wang, J.; Boyd, B. J. (Talanta, 2015)

(untitled) - Vázquez, M. E.; Blanco, J. B.; Salvadori, S.; Trapella, C.; Argazzi, R.; Bryant, S. D.; Jinsmaa, Y.; Lazarus, L. H.; Negri, L.; Giannini, E.; Lattanzi, R.; Colucci, M.; et al. (J. Med. Chem., 2006)

(untitled) - Oh, K. J.; Cash, K. J.; Plaxco, K. W. (Chem. – Eur. J., 2009)

(untitled) - Fischer, P. M. (Curr. Protein Pept. Sci., 2003)

(untitled) - Mitchell, A. R. (Pept. Sci., 2008)

(untitled) - Pavan, S.; Berti, F. (Anal. Bioanal. Chem., 2012)

Methods in Cell Biology - LiCata, V. J.; Wowor, A. J. (Applications of Fluorescence Anisotropy to the Study of Protein–DNA Interactions, 2008)

Methods in Enzymology - Gryczynski, Z.; Gryczynski, I.; Lakowicz, J. R. (Fluorescence-sensing methods, 2003)

(untitled) - Maity, D.; Sarkar, B.; Maiti, S.; Govindaraju, T. (ChemPlusChem, 2013)

(untitled) - Nitz, M.; Mezo, A. R.; Ali, M. H.; Imperiali, B. (Chem. Commun., 2002)

(untitled) - Weber, G.; Farris, F. J. (Biochemistry, 1979)

(untitled) - Uchiyama, S.; Takehira, K.; Yoshihara, T.; Tobita, S.; Ohwada, T. (Org. Lett., 2006)

(untitled) - Oh, K. J.; Cash, K. J.; Plaxco, K. W. (J. Am. Chem. Soc., 2006)

(untitled) - Wang, L.; Hiblot, J.; Popp, C.; Xue, L.; Johnsson, K. (Angew. Chem., Int. Ed., 2020)

(untitled) - Shvadchak, V. V.; Kucherak, O.; Afitska, K.; Dziuba, D.; Yushchenko, D. A. (Biochim. Biophys. Acta, Biomembr., 2017)

(untitled) - Willets, K. A.; Callis, P. R.; Moerner, W. E. (J. Phys. Chem. B, 2004)

(untitled) - Pazos, E.; Pérez, M.; Gutiérrez-de-Terán, H.; Orzáez, M.; Guevara, T.; Mascareñas, J. L.; Vázquez, M. E. (Org. Biomol. Chem., 2011)

(untitled) - Sapsford, K. E.; Blanco-Canosa, J. B.; Dawson, P. E.; Medintz, I. L. (Bioconjugate Chem., 2010)

(untitled) - Thurley, S.; Röglin, L.; Seitz, O. (J. Am. Chem. Soc., 2007)

(untitled) - Chudakov, D. M.; Matz, M. V.; Lukyanov, S.; Lukyanov, K. A. (Physiol. Rev., 2010)

(untitled) - Østergaard, M. E.; Hrdlicka, P. J. (Chem. Soc. Rev., 2011)

(untitled) - Maity, D.; Matković, M.; Li, S.; Ehlers, M.; Wu, J.; Piantanida, I.; Schmuck, C. (Chem. – Eur. J., 2017)

(untitled) - Maity, D.; Jiang, J.; Ehlers, M.; Wu, J.; Schmuck, C. (Chem. Commun., 2016)

(untitled) - Wu, J.; Zou, Y.; Li, C.; Sicking, W.; Piantanida, I.; Yi, T.; Schmuck, C. (J. Am. Chem. Soc., 2012)

(untitled) - Dennis, P. B.; Jaeschke, A.; Saitoh, M.; Fowler, B.; Kozma, S. C.; Thomas, G. (Science, 2001)

(untitled) - Uzman, A. (Biochem. Mol. Biol. Educ., 2003)

(untitled) - Lecca, D.; Ceruti, S. (Biochem. Pharmacol., 2008)

(untitled) - Pullarkat, S. T.; Stoehlmacher, J.; Ghaderi, V.; Xiong, Y.-P.; Ingles, S. A.; Sherrod, A.; Warren, R.; Tsao-Wei, D.; Groshen, S.; Lenz, H.-J. (Pharmacogenomics J., 2001)

(untitled) - Maity, D.; Li, M.; Ehlers, M.; Schmuck, C. (Chem. Commun., 2017)

(untitled) - Hurley, L. H. (Nat. Rev. Cancer, 2002)

(untitled) - Balasubramanian, S.; Hurley, L. H.; Neidle, S. (Nat. Rev. Drug Discovery, 2011)

(untitled) - Maity, D.; Assaf, K. I.; Sicking, W.; Hirschhäuser, C.; Nau, W. M.; Schmuck, C. (Chem. – Eur. J., 2019)

(untitled) - Skoulakis, E. M. C.; Davis, R. L. (Mol. Neurobiol., 1998)

(untitled) - Morrison, D. K. (Trends Cell Biol., 2009)

(untitled) - Boston, P. F.; Jackson, P.; Thompson, R. J. (J. Neurochem., 1982)

(untitled) - Kaplan, A.; Ottmann, C.; Fournier, A. E. (Pharmacol. Res., 2017)

(untitled) - Maity, D.; Gigante, A.; Sánchez-Murcia, P. A.; Sijbesma, E.; Li, M.; Bier, D.; Mosel, S.; Knauer, S.; Ottmann, C.; Schmuck, C. (Org. Biomol. Chem., 2019)

(untitled) - Gosalia, D. N.; Salisbury, C. M.; Ellman, J. A.; Diamond, S. L. (Mol. Cell. Proteomics, 2005)

(untitled) - Tanaka, T.; McRae, B. J.; Cho, K.; Cook, R.; Fraki, J. E.; Johnson, D. A.; Powers, J. C. (J. Biol. Chem., 1983)

(untitled) - Molinari, J. F.; Scuri, M.; Moore, W. R.; Clark, J.; Tanaka, R.; Abraham, W. M. (Am. J. Respir. Crit. Care Med., 1996)

(untitled) - Wang, Q.; Shi, X.; Zhu, X.; Ehlers, M.; Wu, J.; Schmuck, C. (Chem. Commun., 2014)

(untitled) - Mackman, N. (Nature, 2008)

(untitled) - Gandhi, N. S.; Mancera, R. L. (Drug Discovery Today, 2010)

(untitled) - Wallis, D. E.; Lewis, B. E.; Messmore, H.; Wehrmacher, W. H. (Clin. Appl. Thromb./Hemostasis, 1998)

(untitled) - Freedman, M. D. (J. Clin. Pharmacol., 1992)

(untitled) - Maity, D.; Schmuck, C. (Chem. – Eur. J., 2016)

(untitled) - Raetz, C. R. H.; Whitfield, C. (Annu. Rev. Biochem., 2002)

(untitled) - Beutler, B.; Rietschel, E. T. (Nat. Rev. Immunol., 2003)

(untitled) - Wu, J.; Zawistowski, A.; Ehrmann, M.; Yi, T.; Schmuck, C. (J. Am. Chem. Soc., 2011)

(untitled) - Zhou, J.; Tan, S.-H.; Nicolas, V.; Bauvy, C.; Yang, N.-D.; Zhang, J.; Xue, Y.; Codogno, P.; Shen, H.-M. (Cell Res., 2013)

(untitled) - Settembre, C.; Fraldi, A.; Medina, D. L.; Ballabio, A. (Nat. Rev. Mol. Cell Biol., 2013)

(untitled) - Tofaris, G. K. (Mov. Disord., 2012)

(untitled) - Fehrenbacher, N.; Jäättelä, M. (Cancer Res., 2005)

(untitled) - Chen, L.; Wu, J.; Schmuck, C.; Tian, H. (Chem. Commun., 2014)